2020
DOI: 10.1101/2020.06.29.178756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes to zonular tension alters the subcellular distribution of AQP5 in regions of influx and efflux of water in the rat lens

Abstract: ABSTRACTPurposeThe lens utilizes circulating fluxes of ions and water that enter the lens at both poles and exit at the equator to maintain its optical properties. We have mapped the subcellular distribution of the lens aquaporins (AQP0, 1, & 5) in these water influx and efflux zones and investigated how their membrane location is affected by changes in tension applied to the lens by the zonules.Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Results from bafilomycin A1 treatment also provide further evidence that AQP5 functions as a regulatory water channel whose trafficking is inducible in the mammalian lens. Petrova et al has previously demonstrated dynamic AQP5 subcellular localization changes in response to changes in zonular tension via mechanosensitive TRPV1 channel agonism 17,21 . Since AQP5 plasma membrane insertion significantly increases fiber cell water permeability in both mouse and rat lenses 17 , regulation of AQP5 subcellular localization can alter lens water homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from bafilomycin A1 treatment also provide further evidence that AQP5 functions as a regulatory water channel whose trafficking is inducible in the mammalian lens. Petrova et al has previously demonstrated dynamic AQP5 subcellular localization changes in response to changes in zonular tension via mechanosensitive TRPV1 channel agonism 17,21 . Since AQP5 plasma membrane insertion significantly increases fiber cell water permeability in both mouse and rat lenses 17 , regulation of AQP5 subcellular localization can alter lens water homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of AQP5 in maintaining lens homeostasis is implied by its expression in all mammalian lenses studied to date including human 12,[18][19][20] , bovine 12 , mouse 11,12,16,17,[19][20][21] , rat 12,17,21 , rabbit 8 , and dog 22 lenses. Functional studies demonstrate the relationship between AQP5 expression and lens osmotic homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that oral treatment with Hsd ameliorated lens fluid influx and osmotic imbalance in diabetic cataract lenses [ 25 ]. Membrane insertion of TRPV4 and AQP5 was observed in response to accommodation changes [ 10 , 11 ]. As fiber cells differentiate, they lose their cellular organelles and their ability to perform de novo protein synthesis [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the AQP family, AQP0, AQP1, and AQP5 are expressed in lens cells. It was reported that the distribution of TRPV4 in the peripheral fiber cells and AQP5 in the efflux and anterior influx zones altered their subcellular localization in response to mechanical and pharmacologically induced reductions in zonular tension [ 10 , 11 ]. These data suggest that AQPs and TRPVs could exist as a store of channels that could be recruited to the plasma membrane to control the water circulation and intracellular pressure in the lens.…”
Section: Introductionmentioning
confidence: 99%